Vegetation degradation dominates over elevation in structuring fungal communities in alpine meadows - Zhu, Ni; Li, Kexin; Gao, Junmei; Wei, Binmeng; Zhao, Lirong; Liu, Lin; Jia, Suyuan; Zhang, Laiting; Xu, Tengqi; Li, Shixiong; Wang, Yanlong; Wang, Xiaoli; et al. (Frontiers in Microbiology, 2025)
IntroductionAlpine meadows provide a critical natural laboratory for investigating interactions between ecosystem degradation and biogeochemical processes across elevational gradients.MethodsThis study examines how degradation states and elevation (3,700 m vs. 4,300 m) influence soil fungal community composition, diversity, and network architecture in Qinghai-Tibetan Plateau grasslands. Through comparative analysis of degraded and intact meadows, we reveal fundamental shifts in belowground ecology driven by environmental change.ResultsKey environmental parameters showed differential responses: soil organic matter (SOM) decreased significantly with degradation, while soil water content exhibited elevation-dependent patterns (p < 0.05). High-throughput sequencing identified Ascomycota, Mortierellomycota, and Basidiomycota as dominant phyla across all samples. Redundancy analysis (RDA) analysis demonstrated that edaphic factors explained 71.3% of fungal community variation, with SOM emerging as the principal driver (p = 0.001). Interestingly, meadow degradation led to an increase in fungal species diversity, thereby simplifying network complexity. Fungal communities show greater sensitivity to degradation than elevational gradients.DiscussionOur results provide a mechanistic framework for predicting fungal community responses to environmental change, with implications for alpine ecosystem management. Future restoration efforts should prioritize SOM conservation and monitor network properties as early warning indicators of ecosystem degradation.